SEJARAH DAN KONSEP MANAJEMEN PENDIDIKAN - Nasib Tua Lumban Gaol (Jurnal Dinamika Pendidikan, 2020)
Educational management is one of the most needed fields in education institutions and system. Consequently, it is necessary to explore deeply the field. This study is purposed to investigate the history of the educational management and establish its main concept. The result of study identified that the development of the educational management was begun in the United Stated in the middle of nineteenth century. Afterwards, the subject was acknowledged in the end of the nineteenth century in various countries. It developed further in the beginning of twentieth century in Indonesia after decentralization implemented in Indonesian education context. Another finding is the four main concepts of the educational management, namely: (1) as an applied science field of management contextualized towards the field of education; (2) associated with managing various educational resources; (3) has the fundamental principles consisting of the efficiency and effectiveness; and (4) focus on the achievement of certainly educational aims. Contributions of the study for theory and practices are discussed further. Keywords: Indonesia, educational leadership, educational management